2021
DOI: 10.1371/journal.pone.0250663
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Scutellaria baicalensis induces semaphorin 3A production in human epidermal keratinocytes

Abstract: In a disease-state-dependent manner, the histamine-resistant itch in dry skin-based skin diseases such as atopic dermatitis (AD) and xerosis is mainly due to hyperinnervation in the epidermis. Semaphorin 3A (Sema3A) is a nerve repulsion factor expressed in keratinocytes and it suppresses nerve fiber elongation in the epidermis. Our previous studies have shown that Sema3A ointment inhibits epidermal hyperinnervation and scratching behavior and improves dermatitis scores in AD model mice. Therefore, we consider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Although few reports on the treatment of AD with SEMA3A in humans have been published, one report described that the topical application of SEMA3A protein improved pruritus and disease activity in an AD mouse model [ 18 ]. It has also been reported that baicalein, a component of Chinese herbal medicines, increases SEMA3A expression in human keratinocytes [ 19 ]. However, to the best of our knowledge, no reports on topical agents that increase SEMA3A expression have been published, and the mechanism by which SEMA3A is regulated remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although few reports on the treatment of AD with SEMA3A in humans have been published, one report described that the topical application of SEMA3A protein improved pruritus and disease activity in an AD mouse model [ 18 ]. It has also been reported that baicalein, a component of Chinese herbal medicines, increases SEMA3A expression in human keratinocytes [ 19 ]. However, to the best of our knowledge, no reports on topical agents that increase SEMA3A expression have been published, and the mechanism by which SEMA3A is regulated remains unclear.…”
Section: Introductionmentioning
confidence: 99%